Understanding perceptions of stigma and accessibility for persons with disabilities in tourism infrastructure and public spaces the case of Quezon City - Nanca, Aileen E.
This study investigated how perceptions of stigma and accessibility among Persons with Disabilities (PWD) are shaped by the Social, Biopsychosocial, and Geospatial Models of Disability within the context of tourism infrastructure and public spaces in Quezon City. It combines qualitative interviews with PWDs, key informant interviews with urban planning and tourism experts, local government officials, and heads of PWD Affairs Offices (PDAO), along with a quantitative survey.